AVALIAÇÃO DA ATIVIDADE CICATRIZANTE DE FLAVONOIDES: UMA REVISÃO SISTEMÁTICA - Cunha, Mylena Mylana Freire da (2022)
Bone flavonoids have wide biological application, such as antioxidant, antimicrobial, antifibrotic, anti-inflammatory and healing activity, therefore, they have been the focus of research. Thus, this work aimed to evaluate the activity of flavonoids in wound healing in humans, through a systemic review. A systemic search was carried out in PubMed/Medline and Scopus electronic databases, without time and language restrictions. Randomized clinical studies that swallow patients with some type of wound, who receive treatment with isolated substances or combinations of a class of flavonoids for their inclusion. This work was prepared in accordance with the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist (PRISMA) and the Cochrane Handbook for Systematic Reviews of Interventions. Initially, 1173 items were retrieved from the databases, after excluding duplicates. Faith then performed a screening step, which resulted in 19 items included for the eligibility step. Of these, 8 articles were included for data protection, analysis and synthesis. Among the studies, four analyzed venous ulcers, evaluated skin wounds, observed lesions in diabetic feet and one evaluated healing in immature feet. The evaluated flavonoids were silymarin, epigallocatechin, diosmin, hisperidine and rutin, isolated or combined. Regarding comparator groups, most (n=5) studies used placebo. Treatment time varies from 4 to 24 weeks. All studies resulted in improvement of the healing process of different wound evaluations, such as decreased wound diameter, shorter healing time, decreased risk of infection, lower risk of infection and inflammation, increased elastin, pain relief and favoring the hydration. Finally, the reading and evaluation of these studies help us to understand and develop alternatives for care, treatment and healing of wounds. In addition, emphasize the need for new randomized clinical trials to establish the therapeutic therapy of the use of flavonoids in this process.